2002
DOI: 10.1523/jneurosci.22-04-01385.2002
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Actions of Brain-Derived Neurotrophic Factor and Neurotrophin-3 on Firing Features and Ion Channel Composition of Murine Spiral Ganglion Neurons

Abstract: It is now well established that sensory neurons and receptors display characteristic morphological and electrophysiological properties tailored to their functions. This is especially evident in the auditory system, where cells are arranged tonotopically and are highly specialized for precise coding of frequency-and timing-dependent auditory information. Less well understood, however, are the mechanisms that give rise to these biophysical properties. We have provided insight into this issue by using whole-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
146
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 91 publications
(97 reference statements)
16
146
1
Order By: Relevance
“…7D) from P6 to P14 (NT-3 exposed: P6, Ϫ47.2 Ϯ 1.4 mV; P8, Ϫ48.9 Ϯ 1.0 mV; P10, Ϫ47.4 Ϯ 1.0 mV; P14, Ϫ46.9 Ϯ 0.8 mV; see figure for statistical comparisons). In contrast to basal neurons, apical neurons responded less robustly across all ages, which is consistent with a previous report (Adamson et al, 2002a; see figure legend for details). The effects of NT-3 on basal neurons suggest that timing features such as latency and APmax (which may be a mixture of timing and excitability) are regulated differently than voltage threshold in response to trkC activation.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…7D) from P6 to P14 (NT-3 exposed: P6, Ϫ47.2 Ϯ 1.4 mV; P8, Ϫ48.9 Ϯ 1.0 mV; P10, Ϫ47.4 Ϯ 1.0 mV; P14, Ϫ46.9 Ϯ 0.8 mV; see figure for statistical comparisons). In contrast to basal neurons, apical neurons responded less robustly across all ages, which is consistent with a previous report (Adamson et al, 2002a; see figure legend for details). The effects of NT-3 on basal neurons suggest that timing features such as latency and APmax (which may be a mixture of timing and excitability) are regulated differently than voltage threshold in response to trkC activation.…”
Section: Resultssupporting
confidence: 92%
“…The data in Figure 2 provide an analysis of rate/level functions to illustrate the wide dynamic range of spiral ganglion neuron firing properties. Representative current-clamp recordings, chosen to illustrate the breadth of individual response profiles, were categorized as described previously Adamson et al, 2002a) and based on Figure 1, RA or SA. These recordings were characterized according to the number of APs elicited over a large voltage range (RA, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible mechanism by which BDNF might cause changes in SGC function is modulation of voltage-gated ion channel expression, distribution, and activity. In in vitro experiments, Adamson et al (2002) showed that redistribution of ion channels causes basal SGCs to exhibit apical firing properties (sustained firing) after NT-3 treatment and apical SGCs to display basal firing properties (phasic firing) after BDNF treatment. It is therefore possible that the eCAP changes we observed in BDNF-treated cochleas reflected a more "basal" composition of the SGC population.…”
Section: Effect Of Bdnf On Ecap Measuresmentioning
confidence: 99%
“…The transient BDNF-induced increase in SGC size may initially affect temporal responsiveness because membrane capacitance is linearly related to soma diameter (Limó n et al, 2005). Additionally, because BDNF treatment causes apical neurons to change from continuously firing to rapidly adapting under constant depolarization (Adamson et al, 2002), slower recovery arguably is a logical consequence of BDNF treatment.…”
Section: Effect Of Bdnf On Ecap Measuresmentioning
confidence: 99%